A political economy of the Middle East - Cammett, Melani Claire; Diwan, Ishac; Richards, Alan; Richards, Alan
"A Political Economy of the Middle East is the most comprehensive analysis of developments in the political economy of the region over the past several decades, examining the interaction of economic development processes, state systems and policies, and social actors in the Middle East. The fourth edition, with new authors Melani Cammett and Ishac Diwan, has been thoroughly revised, with two new introductory chapters that provide an updated framework with which to understand and study the many changes in demography, education, labor markets, urbanization, water and agriculture, and international labor migration in recent years. The new edition also includes: a new chapter that charts the political economy of the Gulf states and, in particular, the phenomenal growth of oil economies; a new chapter on the rise of "crony capitalism;" and increased coverage of the changes in civil society and social movements in the region, including an exploration of the causes, dynamics, consequences, and aftermath of the Arab uprisings"--
Includes bibliographical references (pages 523-566) and index.
Keywords: Working class -- Middle East; POLITICAL SCIENCE / Economic Conditions; HISTORY / Middle East / General; BUSINESS & ECONOMICS / Development / Economic Development